Developing Numeration Literacy Intelligence through Pairing Activities for Children Aged 4-5 Years at PAUD Terpadu Plus Al Karimah - Mardiah Mardiah; Hikmah; Firdha Hayati (Tajdid Al-Athfal, 2023)
Numeracy are two skills that develop from an early age and become important factors that determine academic success later in life. Children demonstrate basic critical, creative, and collaborative thinking skills. Children can recognize and see relationships between patterns, symbols and data, and can use them to solve problems in everyday life. Numeracy skills in early childhood are also related to basic problem-solving abilities and the application of mathematics in everyday life. Not just number counting skills, but also includes algebraic thinking, geometry, measurement, data analysis and chance. The knowledge, skills, behaviors, and tendencies a person needs to be able to use math in a variety of situations. The knowledge, skills, behaviors, and tendencies a person needs to be able to use math in a variety of situations. Numeration refers to the basics of mathematical reasoning acquired at an early age. This study examines numeracy intelligence through pairing activities. The subjects of this study were group A children in PAUD Terpadu Plus Al-karimah as many as 16 children.